Exploiting Epigenetic Variations for Crop Disease Resistance Improvement - Zhi, Pengfei; Chang, Cheng (Frontiers in Plant Science, 2021)
Pathogen infections seriously threaten plant health and global crop production. Epigenetic processes such as DNA methylation, histone post-translational modifications, chromatin assembly and remodeling play important roles in transcriptional regulation of plant defense responses and could provide a new direction to drive breeding strategies for crop disease resistance improvement. Although past decades have seen unprecedented proceedings in understanding the epigenetic mechanism of plant defense response, most of these advances were derived from studies in model plants like Arabidopsis. In this review, we highlighted the recent epigenetic studies on crop-pathogen interactions and discussed the potentials, challenges, and strategies in exploiting epigenetic variations for crop disease resistance improvement.